PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS IV SD NEGERI 15 PANGKALAN NYIRIH RUPAT - Multajim Multajim; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was conducted because of the low of IPS study result of fourth grade students of SD Negeri 15 Pangkalan Nyirih, Minimum Criteria of completion in school, that is 70. From 26 students, reaching KKM only 10 students (38,46%), while students who have not reached the KKM there are 16 students (61.63%) with an average grade grade of 65.38. To overcome these problems, the researchers apply guided inquiry learning model. The purpose of this study was to improve the learning outcomes of IPS in the fourth grade students of SD Negeri 15 Pangkalan Nyirih with the implementation of guided inquiry learning model. The results of the study authors note the average value of the basic score of 65.38 average value increased in the first cycle of 17.06% to 76.54. In cycle II the average score of students also increased by 29.42% to 84.62. At the basic score of classical completeness of learning result of IPS student is 38.46% (not complete). After applied in guided inquiry learning model in cycle I, student's completeness of classical learning increased to 76,92% and in cycle II, student's classical learning completeness increased to 92,30%. Teacher activity at the first meeting of the first cycle of the percentage was 70.83,% with sufficient category. The second meeting increased to 83.33% with good category. At the first meeting of the second cycle of teacher activity increased to 91.66% with very good category. At the second meeting it increased to 95.83% with very good category. Student activity at first meeting of cycle I the percentage is 58% with less category. The second meeting increased to 69% with sufficient category. At the first meeting of the second cycle of student activity increased to 85% with good category. At the second meeting it increased to 96% with very good category. The increase of teacher and student activity percentage was also accompanied by the increase of the average score of students' learning outcomes from the basic scores (65,38) at the end of cycle II to 96. From the analysis of research data, it can be concluded that the application of guided inquiry learning model can improve learning outcomes IPS in fourth grade students of SD Negeri 15 Pangkalan Nyirih Rupat.Keywords: Inquiry of learning result of IPS